ANALISIS HUBUNGAN LOYALITAS TERHADAP KINERJA PEGAWAI DI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KLAS II PONTIANAK - B31107136, Rinche Feberanty (Jurnal Manajemen Update, 2013)
This study discusses the relationship of loyalty to employee performance Kesyahbandaran Office and the Port Authority of Class II Pontianak. Employee loyalty has a very important role for the development of an organization. Besides the engine driving productivity, loyalty also can improve work performance and employee commitment to always provide the best for the organization and a strong loyalty has a major impact on work performance (performance) employees. The research method used is descriptive. The population in this study amounted to 147 people. The sample amounted to 60 people. The sample in this study was determined using the method of proportional stratified random sampling or stratified random sampling in proportion using the formula Slovin. Questionnaire instrument is used as a means of collecting data. The results of multiple linear regression analysis showed that employee loyalty is a significant effect on employee performance. Loyalty has a positive and significant impact on employee performance. Keywords: Transformational Leadership, Organizational Culture, Employee Performance.